Becoming a scholar : cross-cultural reflections on identity and agency in an education doctorate - Savva, Maria; Nygaard, Lynn P. (UCL Press, 2021)
In Becoming a Scholar nine mature, part-time, international students reflect on the transformation they each underwent while enrolled in a professional doctorate programme. Their narratives provide breadth and depth to themes that represent a diverse cross-section of cultures, identities and communities.